A descriptive correlational study to assess the relationship between emotional intelligence and assertive behaviour among nursing students at a selected nursing college, Bangalore. India - S., Prof. Nandakumar (International Journal of Advanced Nursing Studies, 2024)
A descriptive correlational study to assess the relationship between emotional intelligence and assertive behaviour among nursing students at a selected nursing college, Bangalore. India. The study objectives were to assess the level of emotional intelligence and the level of assertive behaviour among nursing students and also to find out the relationship between emotional intelligence and assertive behaviour among nursing students. Non probability convenient sampling was used to select 50 participants. The investigator after getting formal written permission from the Principal and selected a list of nursing students who fulfilled the sampling criteria and selected 50 participants after getting oral consent from them. The investigator collected the data by using the Schutte self-report rating scale to assess the level of emotional intelligence and also used Robert E. Alberti assertiveness inventory to assess the level of assertive behavior using Google forms as a platform to collect the data. 30 minutes was given for each participants for the data collection. The reliability and validity of the tool was established by 3 experts. The study result found that it was 6 (12%)participants had low level of Emotional Intelligence, 25 (50%) had moderate level of Emotional Intelligence and 19(38%) had high level of Emotional Intelligence. And also it was found that 10(20%) were shown less Assertive Behaviour, 28 (56%) were shown moderately Assertive Behaviour and 12(24%) of them were shown highly Assertive Behaviour. This study found that there was a relationship exists between the level of emotional intelligence while comparing with the level of assertive behaviour. The correlation coefficient value between the level of emotional intelligence and level of Assertive behaviour was found to be r=0.284 which indicates that there was a positive relationship between the variables.